PENGEMBANGAN PESANTREN MELALUI ANALISIS SWOT: TANTANGAN DAN PELUANG DI ERA VUCAH - Tansah, Lala; Basri, Hasan; Suhartin, Andewii (Sindoro: Cendikia Pendidikan, 2024)
This study aims to analyze the development of Islamic boarding schools (pesantren) in Indonesia using the SWOT analysis approach. Considering the ever-changing educational context, especially in the VUCAH era (Volatile, Uncertain, Complex, Ambiguous, Hyper-Connectivity), this research explores the strengths, weaknesses, opportunities, and threats faced by pesantren in their efforts to improve educational quality and relevance. This study adopts a qualitative approach to gain an in-depth understanding of the internal and external dynamics encountered by pesantren, as well as how they formulate development strategies in response to the challenges and opportunities present. The analysis reveals that pesantren possess strengths such as a strong tradition of education and community support but also face weaknesses related to access to modern resources. Opportunities for integrating information technology and threats from formal educational institutions represent challenges that need to be addressed. Based on these findings, development recommendations include curriculum innovation, capacity building for educators, and promoting a positive image of pesantren. With these steps, pesantren are expected to prepare students (santri) to face future challenges and contribute to character education in Indonesia. Keywords: Pesantren development, SWOT analysis, Islamic education, VUCAH, curriculum innovation, education quality.